Pregnancy in reflux nephropathy – our experience. (7th June 2011) - Nisal, M K; Hall, M; Yasmaras, B; Carr, S; Singhal, T
Abstract : Reflux nephropathy, a leading cause of chronic renal failure in women of childbearing age, leads to pregnancy and neonatal complications and poses risk to babies due to autosomal dominant inheritance. We analysed pregnancies in women with reflux nephropathy. Data were collected retrospectively from maintained database and case notes of pregnancies in a university hospital between 2004–2009. Results: 24 women, mean age 30.15 years (±5.19) had 26 pregnancies. Mean peak creatinine significantly increased during pregnancy from 74.68 to 86.49 (p=0.0034). Eight women had preeclampsia. Four out of five women (80%) who had peak creatinine above 110 µmol/l had fetal growth restriction. None of the 15 women who were followed up at 1 year had deterioration in renal function. Eight were not followed up in view of normal renal function at delivery. Nine (34%) women underwent induction of labour due to worsening of creatinine. Vescicoureteric reflux was excluded in 15 babies who had renal ultrasound scan at 6 weeks postnatal period. 11 babies had no imaging studies. Conclusions: We report series of 26 successful pregnancies in women with reflux nephropathy. Although there was significant rise in creatinine during pregnancy, it did not affect the pregnancy outcome significantly. Though more than one third of pregnancies required induction of labour due to worsening creatinine, there was no deterioration of renal function at 1 year postdelivery follow-up. Almost all the babies born to mother with peak pregnancy creatinine >110 µmol/l had growth retardation. Ultrasound scan did not identify vescicoureteric reflux in babies of these patients.